Open Channel Surges - Pandey, Bharat Raj (Journal of Advanced College of Engineering and Management, 2016)
The open channel Surges due to sudden changes of flow depth creates Celerity (Wave Velocity) in the flow in addition to the normal water velocity of the channels. These waves travel in the downstream and sometimes upstream of the channels depending on the various situations. The propagation of the Surges becomes positives or negatives depending on its crest and the trough of the waves. Therefore, on this topic, these principals are presented in the analytical methods. Journal of Advanced College of Engineering and Management, Vol. 1, 2015, pp. 35-43